2010
DOI: 10.1007/s11269-010-9710-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Safe Yield Policy Implementation

Abstract: The presented method enhances groundwater-mandated safe yield management. It is useful for settings that prevent sustained yield or integrated management. To protect hydraulically connected surface water rights, the Utah government's Cache Valley groundwater management plan proposes that total pumping increase not exceed 84,431 m 3 /day. To determine how best to spatially distribute additional allowable pumping, stakeholders quantified limits defining acceptable impacts on selected water resource indicators. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Perennialyield strategies generally are designed to be protective from year to year without much consideration of issues during a year (ASCE 1987). For perennial-yield planning, modelers often employ steady-state simulation models that compute the same equilibrium aquifer conditions as SVs computed by transient models simulated for a very long time (Peralta et al 2011). If one is simulating transient monthly pumping rates that are in harmony with a perennial-yield annual pumping strategy, heads and stored groundwater volume change during the year, but net annual storage change is virtually nil.…”
Section: Traditional Simulation-optimization Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Perennialyield strategies generally are designed to be protective from year to year without much consideration of issues during a year (ASCE 1987). For perennial-yield planning, modelers often employ steady-state simulation models that compute the same equilibrium aquifer conditions as SVs computed by transient models simulated for a very long time (Peralta et al 2011). If one is simulating transient monthly pumping rates that are in harmony with a perennial-yield annual pumping strategy, heads and stored groundwater volume change during the year, but net annual storage change is virtually nil.…”
Section: Traditional Simulation-optimization Modelingmentioning
confidence: 99%
“…This cycling method has been applied to a wide range of S-O studies involving nonlinear aquifer systems and the reported optimal strategies have accurately satisfied SV constraints (Takahashi and Peralta 1995;Peralta et al 2011).…”
Section: Addressing Nonlinear Aquifers By Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, the determination of the coastal groundwater discharges under different scenarios is important to analyze management alternatives (Zhou, 2014;Hugman et al, 2015). The classical sustainable and optimal yield concept has been extensively applied to analyze groundwater management problems (Peralta et al, 2011;Mays, 2013). It could be also applied to study sustainability in coastal aquifers management (Don et al, 2006;McCoy and Corbett, 2009;Liu and Dai, 2012;El-Kadi et al, 2014;Unsal et al, 2014;).…”
Section: Introductionmentioning
confidence: 99%